2014
DOI: 10.1111/jpi.12114
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin improves neuroplasticity by upregulating the growth‐associated protein‐43 (GAP‐43) andNMDARpostsynaptic density‐95 (PSD‐95) proteins in cultured neurons exposed to glutamate excitotoxicity and in rats subjected to transient focal cerebral ischemia even during a long‐term recovery period

Abstract: Recent evidence shows that the NMDAR postsynaptic density-95 (PSD-95), growth-associated protein-43 (GAP-43), and matrix metalloproteinase-9 (MMP-9) protein enhance neuroplasticity at the subacute stage of stroke. Here, we evaluated whether melatonin would modulate the PSD-95, GAP-43, and MMP-9 proteins in cultured neurons exposed to glutamate excitotoxicity and in rats subjected to experimental stroke. Adult male Sprague-Dawley rats were treated with melatonin (5 mg/kg) or vehicle at reperfusion onset after t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
45
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(48 citation statements)
references
References 54 publications
2
45
0
1
Order By: Relevance
“…For example, melatonin may prevent oxidative damage in a model of focal ischemia by enhancing the nuclear factor erythroid 2-related factor 2 and antioxidant-responsive element (Nrf2-ARE) signaling pathway [219]. Moreover, melatonin may prevent glutamate excitotoxicity by up-regulating the growthassociated protein-43 (GAP-43) and NMDAR postsynaptic density-95 (PSD-95) proteins, thereby enhancing neuroplasticity [221]. Melatonin may also prevent ER stress [222] In a multicenter RCT melatonin combined with buspirone was effective for the acute treatment of MDD [223].…”
Section: Melatoninmentioning
confidence: 98%
See 1 more Smart Citation
“…For example, melatonin may prevent oxidative damage in a model of focal ischemia by enhancing the nuclear factor erythroid 2-related factor 2 and antioxidant-responsive element (Nrf2-ARE) signaling pathway [219]. Moreover, melatonin may prevent glutamate excitotoxicity by up-regulating the growthassociated protein-43 (GAP-43) and NMDAR postsynaptic density-95 (PSD-95) proteins, thereby enhancing neuroplasticity [221]. Melatonin may also prevent ER stress [222] In a multicenter RCT melatonin combined with buspirone was effective for the acute treatment of MDD [223].…”
Section: Melatoninmentioning
confidence: 98%
“…The neuroprotective effects of melatonin have been extensively investigated [219][220][221]. For example, melatonin may prevent oxidative damage in a model of focal ischemia by enhancing the nuclear factor erythroid 2-related factor 2 and antioxidant-responsive element (Nrf2-ARE) signaling pathway [219].…”
Section: Melatoninmentioning
confidence: 99%
“…Recently, the antioxidant effects of melatonin-induced neural plasticity have been investigated and other studies have reported the effects of melatonin on neuroplasticity and brain remodeling [49]. According to former researchers, melatonin seems to more effectively prevent lipid peroxidation in vivo [50], indicating that an even higher concentration of melatonin is thought to be required to exert its antioxidative role in vitro conditions compared to in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…And overproduction of ROS due to the lack of FMRP has observed in Fmr1 KO mice. Eventually, these events affect neural signaling, learning and memory problem caused by altered antioxidant system [44]. Recently, melatonin has been investigated in neuronal plasticity with its antioxidant effect.…”
Section: Introductionmentioning
confidence: 99%